From Reductionism Toward Integration: Understanding How Social Behavior Emerges From Integrated Circuits - Dickinson, Sarah Y.; Kelly, Diane A.; Padilla, Stephanie L.; Bergan, Joseph F. (Frontiers in Integrative Neuroscience, 2022)
Complex social behaviors are emergent properties of the brain’s interconnected and overlapping neural networks. Questions aimed at understanding how brain circuits produce specific and appropriate behaviors have changed over the past half century, shifting from studies of gross anatomical and behavioral associations, to manipulating and monitoring precisely targeted cell types. This technical progression has enabled increasingly deep insights into the regulation of perception and behavior with remarkable precision. The capacity of reductionist approaches to identify the function of isolated circuits is undeniable but many behaviors require rapid integration of diverse inputs. This review examines progress toward understanding integrative social circuits and focuses on specific nodes of the social behavior network including the medial amygdala, ventromedial hypothalamus (VMH) and medial preoptic area of the hypothalamus (MPOA) as examples of broad integration between multiple interwoven brain circuits. Our understanding of mechanisms for producing social behavior has deepened in conjunction with advances in technologies for visualizing and manipulating specific neurons and, here, we consider emerging strategies to address brain circuit function in the context of integrative anatomy.